2004
DOI: 10.1055/s-2004-832685
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and 5-HT2CReceptor Polymorphism: A HMPAO-SPECT Study in Healthy Male Probands Using mCPP-Challenge of the 5-HT2CReceptor

Abstract: These findings suggest that differences in the 5-HT (2C) receptor gene polymorphism has functional consequences due to a different responsiveness of the expressed 5-HT (2C) receptor variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Despite this relevance, there is poor experiment evidence on animals and genetic investigations that focused on this part of the brain with a specific attention devoted to the serotonin receptor 2C. Anyway, a recent interesting experiment reported that the presence of the Ser or Cys allele of the well known rs6318 mutation is associated with a list of diverse distributions of the blood flow in the brain of normal subjects [Kuhn et al, 2004]. …”
Section: Anterior Cingulate Relevance To Psychiatric Disordersmentioning
confidence: 99%
“…Despite this relevance, there is poor experiment evidence on animals and genetic investigations that focused on this part of the brain with a specific attention devoted to the serotonin receptor 2C. Anyway, a recent interesting experiment reported that the presence of the Ser or Cys allele of the well known rs6318 mutation is associated with a list of diverse distributions of the blood flow in the brain of normal subjects [Kuhn et al, 2004]. …”
Section: Anterior Cingulate Relevance To Psychiatric Disordersmentioning
confidence: 99%
“…Identification and validation of single nucleotide polymorphisms ( SNPs ) that predict impulsivity, cue reactivity or treatment success could also be useful in guiding prevention efforts (Ducci and Goldman, 2012). Impulsivity has been associated with genotypes that predict reduced 5-HT function (Bevilacqua, et al, 2010; Bevilacqua and Goldman, 2013; Bjork, et al, 2002; Stoltenberg, et al, 2012) and we have recently demonstrated that cocaine-dependent subjects who carry a SNP in the HTR2C (rs6318) (Lappalainen, et al, 1995) predicted to alter 5-HT 2C R functionality (Brasch-Andersen, et al, 2011; Kuhn, et al, 2004; Okada, et al, 2004; Walstab, et al, 2011), exhibit significantly higher attentional bias on the cocaine-word Stroop task. As convergent evidence links genotypes to phenotypes important in addictive processes, it will be possible to best understand the shared genetic liability for impulsivity and cue reactivity, and to integrate this information into more effective clinical care for afflicted patients.…”
Section: Implications For Treatment Of Cocaine Addictionmentioning
confidence: 99%
“…Male carriers of the less common Ser23 C allele show a trend toward faster and stronger adrenocorticotropic hormone ACTH responses to the 5HTR2C agonist m-chlorophenylpiperazine (m-CPP) [7], as well as a different pattern of change in regional cerebral blood flow following m-CPP infusion compared to men carrying the 5HTR2C Cys23 G allele [8]. In related work [9] we recently found that rs6318 was associated with stress responses to an emotional stress task in the laboratory.…”
Section: Introductionmentioning
confidence: 99%